Partial Fractions
Partial Fractions
Partial Fractions
3.3 a) = 2 − 2
( s + 1)( s + 4) 3 s + 1 s + 4
2 2
1 1
= 2 2 − 2
s +1 s + 2 2
1 1
L−1 2 2 − 2 = Cost − Cos 2t
s +1 s + 2 2
1 1 A B+C
= = + 2
b) 2
[
s ( s − 2 s + 5) s ( s − 1) + 2
2 2
]
s s − 2s + 5
A+B=0
-2A+C=0
5A=1
A=1/5 ;B=-1/5;C=2/5
1 1 2−s
We get X ( s) = + 2
5 s s − 2 s + 5
Inverting,we get
1 1 t
1 + e Sin 2 t − e t
Cos 2 t
5
=
2
1 1
= 1 + e t Sin 2t − Cos 2t
5 2
3s 2 − s 2 − 3s + 2 A B C D
c) = + 2+ +
s ( s − 1)
2 2
s s s − 1 ( s − 1)2
As( s − 1) 2 + B( s − 1) 2 + Cs 2 ( s − 1) + Ds 2 = 3s 3 − s 2 − 3s + 2
A( s 3 − 2 s + s ) + B ( s 2 − 2 s + 1) + C ( s 3 − s 2 ) + Ds 2 = 3s 3 − s 2 − 3s + 2
A+C=3
-2A+B-C+D=-1
A-2B=-3
B=2;
A=2(2)-3=1
C=3-1=2
D=2(1)-2+2-1=1
1 2 2 1
We get X ( s ) = + 2+ +
s s s + 1 ( s − 1) 2
By inverse L.T
L−1 [X (t )] = 1 + 2t + 2e t + te t
L−1 [X (t )] = 1 + 2t + e t ( 2 + t )
3.4 Expand the following function by partial fraction expansion. Do not evaluate
co-efficient or invert expressions
2
X ( s) =
( s + 1)( s + 1) 2 ( s + 3)
2
A Bs + C Ds + E F
X ( s) = + 2 + 2 +
s + 1 s + 1 ( s + 1) 2
s+3
A B C D E F G H
X ( s) = + 2 + 3+ + + + +
s s s s +1 s + 2 s + 3 ( s + 3) 2
( s + 3) 3
A B C D
X ( s) = + + +
s +1 s + 2 s+3 s+4
by comparing powers of s we can evaluate A,B,C,D
1
3.5 a) X ( s ) =
s ( s + 1)(0.5s + 1)
1 A B C
Let = + +
s ( s + 1)(0.5s + 1) s s + 1 (0.5s + 1)
s 2 3s s2
= A + + 1 + B + s + C ( s 2 + s ) = 1
2 2 2
A=1
A B B 1
+ + C = 0= +C = −
2 2 2 2
3A 3
+ B + C = 0= B + C = −
2 2
B/2=1/2 *-3/2=-1;
B=-2;
C= -3/2+2=1/2
1 2 1 1
X ( s) = − +
s s + 1 2 0.5s + 1
= L − 1 ( X ( s )) = x ( t ) = 1 − 2 e − t + e − 2 t
dx
b) + 2 x = 2; x (0) = 0
dt
sX ( s ) − x (0) + 2 X ( s ) = 2 / s
2
L−1 ( X ( s )) =
s ( s + 2)
2
L−1 ( X ( s )) = 2 L−1
s ( s + 2)
1 / 2 1 / 2
= L−1 ( X ( s )) = 2 L−1 −
s s + 2
−2 t
= 1 − e
s +1
3.6 a) Y ( s ) =
s + 2s + 5
2
s +1
= Y ( s) =
s + 2s + 5
2
s +1
=
( s + 1) 2 + 4
s +1
= L−1 (Y ( s )) = L−1
( s + 1) + 4
2
Y (t ) = e − t Cos2t
s 2 + 2s
b) Y ( s ) =
s4
1 2
Y ( s) = 2
+ 3
s s
Y(t)= L−1 (Y ( s )) = t + t 2
2s
c) Y ( s ) =
( s − 1) 3
2s − 2 + 2
=
( s − 1) 3
2 2
= +
( s − 1) 2
( s − 1) 3
2 2
Y (t ) = L−1 2
+ L−1
3
( s − 1) ( s − 1)
t2 t
= 2(te + e = e t (t 2 + 2t )
t
2
1 As + B Cs + D
3.7a) Y ( s) = = +
( s 2 + 1) ( s 2 + 1) ( s 2 + 1)
thus ( As + B ) + (Cs + D )( s 2 + 1) = 1
= Cs 3 + Ds 2 + ( A + C ) s + ( B + D ) = 1
C=0,D=0
Also A=0;B=1
1 1 A B C D
Y ( s) = 2 = = + + +
( s + 1) 2
(s + i) (s − i)
2 2
(s + i) (s + i) 2
(s − i) (s − i)2
A( s + i )( s − i ) 2 + B( s − i ) 2 + C ( s − i )( s + i ) 2 + D( s + i ) 2 = 1
( A + C ) s 3 + ( − Ai + B + Ci + D ) s 2 + ( A − 2 Bi + C + 2 Di ) + ( − Ai − B + Ci − D ) = 1
Thus,A+C=0
-Ai+B+Ci+2Di=0 ; B=D
A-2Bi+C+2Di=0
-Ai-B+Ci-D=1 Also D=-Ci;B=-Ci,
A=-C,C=-i/4
i/4 − 1/ 4 −i/4 − 1/ 4
Y ( s) = + + +
(s + i) (s + i) 2
(s − i) (s − i)2
Y (t ) = 1 / 4(ie − it − te −it − ie it − te it )
Y (t ) = 1 / 4(i (Cost − iSin t ) − t (Cost − i Sin t ) − i(Cos t + iSin t ) − t (Cos t + i Sin t ) )
Y (t ) = 1 / 4( 2 Sin t − 2t Cos t )
Y ( t ) = 1 / 2 ( Sin t − t Cos t)
1
3.8 f ( s) =
s ( s + 1)
2
A B C
= f ( s) = + +
s 2
s s +1
= A( s + 1) + Bs( s + 1) + Cs 2 = 1
f (t ) = (t − 1) + e − t
PROPERTIES OF TRANSFORMS
1 e − s − e −2 s e −3s
f ( s) = + −
s s2 s
1 − e −3s e − s − e −2 s
= +
s s2